Psychosocial and health problems associated with alcohol use disorder and cannabis use disorder in U.S. adults. (1st December 2021) - Gutkind, Sarah; Fink, David S.; Shmulewitz, Dvora; Stohl, Malka; Hasin, Deborah
Abstract: Background: Although the problems associated with alcohol use disorder (AUD) are well known, little is known about the psychosocial problems associated with cannabis use disorder (CUD), and the harmfulness of CUD relative to AUD. We compared the odds of psychosocial and health-related problems between individuals with DSM-5 AUD-only, CUD-only and co-occurring AUD+CUD. Methods: The 2012–2013 NESARC-III, a nationally representative cross-sectional survey of non-institutionalized US adults (n = 36, 309), assessed participants for DSM-5 AUD, CUD, and psychosocial (interpersonal, financial, legal) and health-related problems. Based on their responses, participants were categorized into mutually exclusive groups: no AUD/CUD, AUD-only, CUD-only, and AUD+CUD. Multivariable logistic regression models examined the associations between psychosocial problems and the four AUD/CUD groups, adjusting for sociodemographic characteristics. Results: People with AUD-only, CUD-only, and AUD+CUD had higher odds of most interpersonal problems (adjusted odds ratio [aORs] 1.07–4.01), financial problems (aORs 1.53–4.28), legal problems (aORs 3.34–7.71), and health-related problems (aORs 1.29–1.92). The odds of psychosocial and health-related problems were similar for CUD-only and AUD-only in direct comparisons. Compared to those with AUD-only, those with AUD+CUD had higher odds of most problems examined (aORs 1.42–2.31). In contrast, there were few differences when comparing AUD+CUD with CUD-only. Conclusions: AUD and CUD were similarly associated with interpersonal, financial, and legal problems, emergency treatment and suicide attempt. People with AUD+CUD had higher odds of certain problems than individuals with either AUD-only or CUD-only. Although most people who use cannabis do not experience harms, our results indicate that CUD does not appear to be less harmful than AUD. Highlights: Cannabis use and cannabis use disorder (CUD) are increasing in the USA. Relations of CUD to psychosocial/health problems were evaluated and compared to AUD. CUD was associated with interpersonal, financial, legal, and health problems. CUD and AUD were associated with similar levels of psychosocial/health problems. Co-occurring AUD+CUD was associated with greatest odds of all problems.